A Phase I clinical and pharmacological study of cis-diamminedichloro(2-methylpyridine) platinum II (AMD473) - Beale, P (Nature Publishing Group, 2003)
AMD473 is a novel sterically hindered platinum cytotoxic with demonstrated ability to overcome acquired resistance to cisplatin in vitro and in human tumour xenografts. A single-agent dose escalating Phase I study was performed. AMD473 was initially administered intravenously as a 1 h infusion every 21 days to patients with advanced solid tumours. In total, 42 patients received a total of 147 cycles (median 3, range 1–8) of treatment at doses of 12, 24, 48, 96, 110, 120, 130, and 150 mg m(−2). Dosing intervals of 21 and 28 days were explored at the recommended dose. Neutropenia and thrombocytopenia proved dose limiting. Other toxicities included moderate nausea, vomiting, anorexia, and a transient metallic taste. There was no significant alopecia. The maximum tolerated dose was 150 mg m(−2). Plasma pharmacokinetics were linear. Two patients with heavily pretreated ovarian cancer showed partial response. Five patients (mesothelioma, ovary, nonsmall cell lung, and melanoma) showed prolonged stable disease. AMD473 demonstrates encouraging activity in patients, including those with prior platinum exposure. Toxicity is predictable with linear pharmacokinetics, as was predicted by preclinical studies. A dose of 120 mg m(−2) every 21 days is recommended for Phase II evaluation although there is evidence that chemo-naive patients and those of good performance status may tolerate a higher dose.